Solve x saga: interactive adventure game-based learning in basic algebra for primary school students - Muhammad Nur Ismail, Mohamad Nurshahnazim; Yahya, Muhammad Amir Yaakub; Mohamad Kamal, Nabil Hakim; Badarul Aza, Akmal Shafiq (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Solve X Saga is an innovative and interactive educational game designed to address the challenges of student disengagement and difficulties in understanding introductory algebra, particularly among primary school students. Algebra, often perceived as abstract and intimidating, can hinder confidence and learning progression in young learners. This game reinvents the learning experience by incorporating problem-solving into an engaging narrative-driven format, where students solve addition and subtraction problems involving one variable to advance through checkpoints. Developed using PowerPoint, Solve X Saga is accessible and easily implemented in classrooms, requiring no additional software. Its unique features include interactive tasks, instant feedback, and tutorial videos, making learning enjoyable and effective. By combining storytelling with mathematics, the game encourages active participation, enhances conceptual understanding, and fosters a positive attitude toward algebra. The game’s advantages include its low cost, scalability, and adaptability to different languages and curricula, ensuring widespread applicability. It contributes to socioeconomic development by equipping students with foundational skills essential for future academic success while providing teachers with a practical, resource-friendly tool. Solve X Saga has significant commercialization potential, with possibilities for global adoption via subscription models, one-time purchases, or educational software bundles.